Teledentistry for Improving Access To, and Quality of Oral Health Care: Overview of Systematic Reviews and Meta-Analyses - Pascaline Kengne Talla; Paul Allison; André Bussières; Anisha Rodrigues; Frédéric Bergeron; Nicolas Giraudeau; Elham Emami (Journal of Medical Internet Research)
Abstract BackgroundDigital interventions including teledentistry are promising approaches to address some of the inadequacies of health care systems. Despite existing systematic reviews (SRs) on the benefits, implementation challenges, accuracy, and effectiveness of teledentistry, a comprehensive synthesis of evidence on its impacts requires further analysis. ObjectiveThe purpose of this overview of SRs is to summarize evidence on the impacts of teledentistry in promoting access to and enhancing the quality of oral health care. MethodsWe searched electronic databases in MEDLINE (Ovid), Embase (Embase.com), CINAHL (EBSCO), Web of Science, Cochrane Library, and Epistemonikos from inception to March 2024, without date and language restrictions, to identify SRs and meta-analyses. Two independent reviewers performed data selection following the PICOSS (population, intervention, comparison, outcome, and study design) format, as well as the data extraction. We conducted quality assessments using both (A MeaSurement Tool to Assess Systematic Reviews-2) AMSTAR 2 and ROBIS (Risk Of Bias In Systematic reviews) tools. The certainty of evidence and the overlap of the primary studies included in the SRs were assessed. Results were presented in tables and graphs. A narrative synthesis was performed. ResultsThe search yielded 1020 articles, of which 30 SRs were included in the overview. The number of participants across these reviews ranged from 130 to 7913 people. All dimensions of the quality of care were addressed to varying extents, with the domains of effectiveness (22/30, 73%), patient-centered care (14/30, 47%), and efficiency (11/30, 37%) being the most extensively studied. Teledentistry addressed public health challenges by improving access to oral health care and reducing inequities (9/30, 30%) for vulnerable people. The major teledentistry applications were teleconsultation (13/30, 43%), and telediagnosis (9/30, 33%). Teledentistry enhanced patient-clinician communication, quality of life, and care experiences for both patients and providers. However, multilevel barriers must be addressed to ensure its successful implementation (7/30, 23%). Meanwhile, patient safety (8/30, 27%) and equity (1/30, 10%) were the least explored domains, with few reviews addressing adverse outcomes, as well as concerns related to data privacy (3/30, 10%) and confidentiality (2/30, 6%). Several SRs exhibited a critically low to low methodological quality (25/30, 83%) and a high risk of bias (8/30, 27%). The overlap (corrected covered area) of the primary studies in all the SRs was slight (30/30, 2.3%), while it was moderate (11/30, 5.7%) for SRs with meta-analyses. ConclusionsThe findings of this overview suggest that teledentistry is an effective and efficient alternative to in-person oral health care. However, significant concerns regarding the quality of the reviews highlight an urgent need for more methodologically rigorous studies to generate robust and reliable evidence. This is particularly essential to better understand teledentistry’s potential to enhance overall health outcomes and ensure equitable access to care, thereby providing a stronger foundation to guide clinical practices and inform policy decisions.